A supervisory control strategy for the detection and restoration of power transmission failures during peak periods using Petri nets. (October 2017) - Jiang, Zhongyuan; Chen, Xiaoliang; Tang, Mingwei
As the important infrastructure of power transmission systems, the power transmission lines are vulnerable during the peak power transmission periods. They usually meet many faults that may cause large area blackouts because of heavy loads. This article proposes a supervisory control strategy to promote the detection and restoration of power transmission failures during the peak or off-peak periods. The faults occurring in power transmission lines can be detected, and fault restoration schemes can be selected by supervisors. Moreover, the architecture of distributed control systems is proposed to perform message switching among supervisors. A coordination protocol that is executed by each supervisor is proposed to selected fault restoration schemes. The proposed strategy can not only detect and restore power transmission failures but also improve the utilization rate of available loads in power transmission systems. The proposed distributed control systems and coordination protocol are modeled by synchronized Petri nets. The correctness of fault restoration is verified using the mathematical methods of Petri nets. Finally, the complexity of the proposed distributed control systems and coordination protocol is discussed, and a real-world example is given.